Religious Moderation Preaching as a Model of Islamic Guidance and Counseling in the 2024 Political Year: A Case Study of Al-Washliyah, Medan City - Abdul Hafiz harahap; Zainal Arifin; Efi Brata Madya (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This research aims to analyse Al-Washliyah's da’wah in promoting religious moderation in Kota Medan during the politically charged year of 2024. The study addresses the rise in religious politicisation and extremist narratives that threaten social cohesion. Using a qualitative case study design, data were obtained through in-depth interviews, participatory observation, and document analysis, and were analysed thematically to identify strategies, challenges, and impacts. The findings reveal that Al-Washliyah fosters religious moderation through sermons, digital media, interfaith collaboration, and community education, highlighting tolerance, inclusivity, and unity. Organisational strength and leadership commitment support these efforts, whereas misinformation and political polarisation remain major obstacles. In practice, this study provides policymakers and religious institutions with insights into developing effective communication models to sustain harmony during electoral dynamics. It contributes to understanding the roles of local religious organisations in maintaining peace amid political tension. Keywords: religious moderation, al-washliyah, islamic guidance, political year, social harmony